Peningkatan Hasil Belajar dan Kemampuan Pemecahan Masalah melalui Penerapan Belajar Tuntas Pada Siswa MAS NW Penendem - M. Saipul Watoni (Pendidikan Al-Gafari, 2024)
Education is something that everyone must follow. With adequate education, a person will be able to answer global challenges in life. With this education, a person's honor and dignity will be raised, the lower a person's level of education, the more dignity in their environment will also be. This research aims to determine the improvement in learning outcomes and problem-solving abilities through the application of thorough learning in Class X MAS NW Penendem students. The type of research used is Classroom Action Research (PTK) which consists of two cycles and each cycle consists of four stages, namely: planning, implementing actions, observing, and reflecting. The object of this research was determined by taking class X, totaling 23 students. The instruments used for data collection in this research were observation sheets and teacher and student tests. The results of this research were obtained in the first cycle, of the 23 students who took the evaluation test for learning outcomes, 17 students completed it and 6 students did not complete it with an average score of 71 ≤ 75. Meanwhile, for the classical percentage it was 73.91% ≤ 85 %, this means that for evaluating learning outcomes using a KKM of 75 and a KKM of 85%, it can be said to be incomplete and for problem-solving in cycle I the average score is 73.04 with a completion percentage of 60%. This value does not meet the classical learning completeness requirements, namely 85%. 16 students got a score ≥ 75, including the completed study category, and 7 students got a score ≤ 75, including the incomplete learning category. From the second cycle analysis, of the 23 students who took the evaluation test, the average evaluation score was 81.30 with a percentage of 95%. This result shows that the requirements for learning completeness have been achieved, namely 85%, 22 students got a learning result score ≥ 75 Meanwhile, for problem-solving abilities, the average student score is 83 with the percentage of many students completing 96%, and included in the complete learning category.